An IDA-PBC Design with Integral Action for Output Voltage Regulation in an Interleaved Boost Converter for DC Microgrid Applications (2021)
This paper describes the output voltage regulation control for an interleaved connected to a direct current (DC) microgrid considering bidirectional current flows. The proposed controller is based on an interconnection and damping passivity-based control (IDA-PBC) approach with integral action that regulates the output voltage profile at its assigned reference. This approach designs a control law via nonlinear feedback that ensures asymptotic stability in a closed-loop in the sense of Lyapunov. Moreover, the IDA-PBC design adds an integral gain to eliminate the possible tracking errors in steady-state conditions. Numerical simulations in the Piecewise Linear Electrical Circuit Simulation (PLECS) package for MATLAB/Simulink demonstrate that the effectiveness of the proposed controller is assessed and compared with a conventional proportional-integral controller under different scenarios considering strong variations in the current injected/absorbed by the DC microgrid.